2016
DOI: 10.1111/bjh.14428
|View full text |Cite
|
Sign up to set email alerts
|

Sequential chemotherapy followed by reduced‐intensity conditioning and allogeneic haematopoietic stem cell transplantation in adult patients with relapse or refractory acute myeloid leukaemia: a survey from the Acute Leukaemia Working Party of EBMT

Abstract: This study analysed the outcome of 267 patients with relapse/refractory acute myeloid leukaemia (AML) who received sequential chemotherapy including fludarabine, cytarabine and amsacrine followed by reduced-intensity conditioning (RIC) and allogeneic haematopoietic stem cell transplantation (HSCT). The transplants in 77 patients were from matched sibling donors (MSDs) and those in 190 patients were from matched unrelated donors. Most patients (94·3%) were given anti-T-cell antibodies. The incidence of acute gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Although direct comparison of outcomes from our study with those of other early AHST or sequential transplant approaches is not possible, the 2‐year OS of transplanted patients (39 ± 15%) we report is comparable to outcomes reported by the SAL study group of early AHST (Stolzel et al , ; Schetelig et al , ) and to both individual reports of different individual sequential strategies using either FLAMSA (FLAG + amsacrine) or clofarabine‐based chemotherapy followed by cyclophosphamide and low dose total body iradiation (Schmid et al , ) or busulphan‐based RIC platforms (Schneidawind et al , ; Mohty et al , ), and to the pooled outcome data from a recently published registry‐based survey by the European Society for Blood and Marrow Transplantation (EBMT) of patients with AML treated with sequential chemotherapy and AHST (Ringden et al , ). In the latter series, the authors report that the 3‐year OS of patients treated with T‐cell depleted approaches was superior to that of those who received T‐cell replete transplants (31% vs. 20%).…”
Section: Discussionsupporting
confidence: 79%
“…Although direct comparison of outcomes from our study with those of other early AHST or sequential transplant approaches is not possible, the 2‐year OS of transplanted patients (39 ± 15%) we report is comparable to outcomes reported by the SAL study group of early AHST (Stolzel et al , ; Schetelig et al , ) and to both individual reports of different individual sequential strategies using either FLAMSA (FLAG + amsacrine) or clofarabine‐based chemotherapy followed by cyclophosphamide and low dose total body iradiation (Schmid et al , ) or busulphan‐based RIC platforms (Schneidawind et al , ; Mohty et al , ), and to the pooled outcome data from a recently published registry‐based survey by the European Society for Blood and Marrow Transplantation (EBMT) of patients with AML treated with sequential chemotherapy and AHST (Ringden et al , ). In the latter series, the authors report that the 3‐year OS of patients treated with T‐cell depleted approaches was superior to that of those who received T‐cell replete transplants (31% vs. 20%).…”
Section: Discussionsupporting
confidence: 79%
“…The causes of death included relapse (n = 69), infectious diseases (n = 41), GVHD (n = 21), sinusoidal obstruction syndrome (n = 1), thrombotic microangiopathy (n = 1), multiple organs failure (n = 2), primary graft failure (n = 1), and unknown (n = 1) ( Table 3). The 5-year cumulative incidence of NRM was 31% (95% CI, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 23% (95% CI,16-30; p = .114) (Fig. 3a) in HID and MSD groups, respectively.…”
Section: Survivalmentioning
confidence: 99%
“…Subgroup analysis showed that 5-year OS for AML, ALL, and ALAL was 50% (95% CI, 43-57), 43% (95% CI, 36-51), and 40% (95% CI, 27-53) in HID group, respectively, and 44% (95% CI, 38-51), 38% (95% CI, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], and 40% (95% CI, 25-56) in MSD group, respectively, and there was no difference between two groups for each underlying disease (p = .947 for AML; p = .798 for ALL; p = .927 for ALAL).…”
Section: Survivalmentioning
confidence: 99%
“…FLAMSA-RIC was originally developed for relapsed/refractory disease, where it showed promising efficacy with 2-year leukemia-free survival (LFS) and overall survival (OS) rates of 40% and 42%, respectively [5]. A more recent registry study on 267 patients showed a GVHD-free relapse-free survival (GRFS) rate at 3 years of 17.8% and an LFS of 25.6% [6]. In addition, FLAMSA has also been used with encouraging results in high-risk AML patients in CR1 and in AML patients with complex karyotype transplanted as soon as possible following FLAMSA-RIC irrespective of response [7,8].…”
Section: Introductionmentioning
confidence: 99%